Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12872-021-02100-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bioelectrical body and visceral fat indices with anthropometric measures and optimal cutoffs in relation to hypertension by age and gender among Chinese adults

Abstract: Background Few studies have compared bioelectrical body and visceral fat indices with anthropometric measures, or evaluated their optimal cutoffs in relation to hypertension among Asians. We compared the efficiencies of bioelectrical indices (percentage of body fat, PBF; visceral fat area, VFA) with anthropometric measures (body mass index, BMI; waist-hip ratio, WHR) for hypertension and re-evaluated the optimal cutoffs of each index by age and gender. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the Zajac et al study, which investigated the relationship between VFA and metabolic syndrome in the female population, they concluded that metabolic syndrome in women is directly related to the VFA index [ 8 ]. In Zhang et al study, they also concluded that the VFA index in women has a strong relationship with hypertension [ 7 ]. Several studies have reported that in Asians, the distribution of total body fat in the abdomen is higher and the incidence of CVD and metabolic risk factors are higher than in European people with the same BMI [ 37 , 38 ] Therefore, BMI as a predictor of vascular disease or organic vascular dysfunction, it is not suitable especially for Asians [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Zajac et al study, which investigated the relationship between VFA and metabolic syndrome in the female population, they concluded that metabolic syndrome in women is directly related to the VFA index [ 8 ]. In Zhang et al study, they also concluded that the VFA index in women has a strong relationship with hypertension [ 7 ]. Several studies have reported that in Asians, the distribution of total body fat in the abdomen is higher and the incidence of CVD and metabolic risk factors are higher than in European people with the same BMI [ 37 , 38 ] Therefore, BMI as a predictor of vascular disease or organic vascular dysfunction, it is not suitable especially for Asians [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, VAI was proposed as a new anthropometric measure in 2010 [ 6 ]. VFA measures the fat that is stored around a number of critical internal organs, including liver, intestine, and pancreas [ 7 ]. WHR is one of the markers of abdominal obesity and has shown an improved ability to identify cardiovascular disease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of Choi’s study, we further found a greater risk of new-onset hypertension in age < 40 years old for each z score increase in BRI. Similarly, Zhang et al also found that age might influence the relationship between AHIs and hypertension by conducting a cross-sectional survey in 8234 Chinese adults [ 31 ]. These results suggested that it is crucial to choose a proper index for hypertension screening according to the specific age.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were conducted by professional medical staff using standard methods. [4,5] Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS), version 24.0 (SPSS Inc., Chicago, IL, USA) and MedCalc (MedCalc Software, Mariakerke, Belgium). Considering sex differences in adiposity distribution and CHD prevalence, all statistical analyses were stratified by sex.…”
mentioning
confidence: 99%
“…A standard questionnaire was used to collect data on participants’ age, sex, ethnicity, highest educational level achieved, marital status, occupation, personal, and family history of CHD, alcohol drinking, tobacco smoking, and physical exercise. All measurements were conducted by professional medical staff using standard methods [4,5] …”
mentioning
confidence: 99%